Infections by Transovarially Transmitted DMelSV in Drosophila Have No Impact on Ovarian Transposable Element Transcripts but Increase Their Amounts in the Soma. (8th September 2021) - Roy, Marlène; Viginier, Barbara; Mayeux, Camille A; Ratinier, Maxime; Fablet, Marie
Abstract: Transposable elements (TEs) are genomic parasites, which activity is tightly controlled in germline cells. Using Sindbis virus, it was recently demonstrated that viral infections affect TE transcript amounts in somatic tissues. However, the strongest evolutionary impacts are expected in gonads, because that is where the genomes of the next generations lie. Here, we investigated this aspect using the Drosophila melanogaster Sigma virus. It is particularly relevant in the genome/TE interaction given its tropism to ovaries, which is the organ displaying the more sophisticated TE control pathways. Our results in Drosophila simulans flies allowed us to confirm the existence of a strong homeostasis of the TE transcriptome in ovaries upon infection, which, however, rely on TE-derived small RNA modulations. In addition, we performed a meta-analysis of RNA-seq data and propose that the immune pathway that is triggered upon viral infection determines the direction of TE transcript modulation in somatic tissues.